Genetic diversity and population structure analysis of Capsicum annuum cultivated in the Northern region of Ghana using simple sequence repeat markers - Paul Yao Anani; Hypolite Bayor; Benjamin Karikari; Isaac Kodzo Amegbor; George Nyarko; Abdul Rashid Hudu; Maryke Labuschagne (Cogent Food & Agriculture)
Pepper (Capsicum annuum) is an essential spicy crop in sub-Saharan African, however, limited genetic improvement initiatives have been undertaken to enhance its productivity. This study characterized the genetic diversity and population structure of 40 C. annuum accessions using 24 simple sequence repeat (SSR) markers. Profiling C. annuum accessions with 24 SSR markers revealed a total of 39 alleles, with an overall mean of 1.63 alleles per locus. The polymorphic information content and observed heterozygosity of the markers ranged from 0.00 to 0.40 and 0.00 to 0.10, respectively. Phylogenetic analysis using the neighbor-joining method grouped the accessions into six clusters, with no clear pattern of distribution based on their collection locations. Genetic differentiation among sub-populations was high (FST = 0.34–0.71), with a mean FST of 0.57 and average expected heterozygosity of 0.06. Population structure analysis, using an admixture model at a 60% membership threshold, assigned 29 accessions to a single genetic cluster, indicating widespread similarity among the samples. The narrow genetic base observed likely reflects the repeated cultivation of locally adapted or recycled germplasm by farmers. These findings emphasize the need to broaden the genetic base of C. annuum through the introduction of diverse germplasm and structured breeding efforts.